A Cu(111) supported h-BN nanosheet: a potential low-cost and high-performance catalyst for CO oxidation. Issue 34 (14th September 2015) - Lin, Sen; Huang, Jing; Gao, Xiaomei
<x xml:space="preserve">Abstract</x> CO oxidation on h-BNNS/Cu(111).